2023
DOI: 10.3390/ijms24076140
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Organ Injury the Role of Substance P and Its Receptors

Abstract: Tightly controlled inflammation is an indispensable mechanism in the maintenance of cellular and organismal homeostasis in living organisms. However, aberrant inflammation is detrimental and has been suggested as a key contributor to organ injury with different etiologies. Substance P (SP) is a neuropeptide with a robust effect on inflammation. The proinflammatory effects of SP are achieved by activating its functional receptors, namely the neurokinin 1 receptor (NK1R) receptor and mas-related G protein-couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…These alterations show that the dysregulation of intracellular iron accumulation and lipid peroxidation in the liver and lungs in mice arises following CLP-surgery-induced sepsis, indicating that ferroptosis was increased in these tissues in mice with sepsis. Given the roles of the SP-NK1R axis in promoting acute inflammatory response [ 5 , 41 , 42 ] and COX-2 expression [ 27 , 28 , 29 ] in inflammation-related pathological circumstances, it is worth probing into the impact of this axis on the profile of ferroptosis in sepsis. Notably, this study showed that these increases in the concentration of iron and MDA in the liver and lungs in mice following CLP-surgery-induced sepsis were reduced by either the deletion of the Tac1 gene, the pharmacological blockage of NK1R, or the combination of these two methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alterations show that the dysregulation of intracellular iron accumulation and lipid peroxidation in the liver and lungs in mice arises following CLP-surgery-induced sepsis, indicating that ferroptosis was increased in these tissues in mice with sepsis. Given the roles of the SP-NK1R axis in promoting acute inflammatory response [ 5 , 41 , 42 ] and COX-2 expression [ 27 , 28 , 29 ] in inflammation-related pathological circumstances, it is worth probing into the impact of this axis on the profile of ferroptosis in sepsis. Notably, this study showed that these increases in the concentration of iron and MDA in the liver and lungs in mice following CLP-surgery-induced sepsis were reduced by either the deletion of the Tac1 gene, the pharmacological blockage of NK1R, or the combination of these two methods.…”
Section: Discussionmentioning
confidence: 99%
“…Substance P (SP) is an undecapeptide encoded by the Tac1 gene in rodents [ 4 ]. It has been implicated in diverse biological processes and pathological settings, predominantly by activating its functional receptor, named neurokinin 1 receptor (NK1R) [ 5 ]. Increased SP-NK1R signalling has been shown to contribute to aberrant systemic inflammatory response, leading to acute inflammatory injury in multiple organs, including the liver, lungs, and kidney in sepsis [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%